Physical properties of Kelempayan (Neomalarckia cadamba sp.) wood / Nur Sakinah Mohamed Tamat ...[et al.] - Mohamed Tamat, Nur Sakinah; Abd Latib, Nurfaizah; Misfar, Siti Nadzirah; Kasim, Jamaludin (2011)
The physical properties are important factors that influence the workability of a material. The main objective of the study is to determine the physical properties (moisture content and density) of Kelempayan with the diameter of breast height ranging between 35cm to 41cm. Kelempayan was harvested from three trees. The trees were cut into three height levels (bottom, middle and top). Samples were taken from each height level and along the radial direction of the stem (near pith, middle and near bark). The highest density of Kelempayan according to the height level was found at the top portion, followed by middle and bottom portion. Along the radial direction, it was showed that the density was highest at near bark followed by middle and near pith. Percentages of moisture content decreased insignificantly from bottom to top portion.